INNOVATIVE ASSESSMENT TECHNOLOGIES IN MODERN LANGUAGE EDUCATION: THEORETICAL FOUNDATIONS AND IMPLICATIONS FOR CONTEMPORARY PEDAGOGY - YUSUPOV, Otabek Yakubovich (The Lingua Spectrum, 2025)
This article provides a deep theoretical exploration of innovative assessment technologies in modern language education, examining their epistemological foundations, methodological implications, and significance for contemporary pedagogical research. Through an expanded scholarly narrative grounded in linguistic theory, educational measurement, psychometrics, multimodality, and data-driven learning analytics, the paper elaborates on the paradigm shift from traditional summative evaluation toward dynamic, AI-enhanced and research-informed assessment models. Emphasis is placed on the philosophical and methodological frameworks that justify the integration of artificial intelligence, adaptive testing, digital portfolios, multimodal diagnostics, and predictive analytics into higher education assessment systems.